Contoured Foam Cushions Cannot Provide Long-term Protection Against Pressure-Ulcers for Individuals with a Spinal Cord Injury: Modeling Studies. (July 2015) - Shoham, Naama; Levy, Ayelet; Kopplin, Kara; Gefen, Amit
ABSTRACT: OBJECTIVE: To determine changes in internal soft-tissue loads in the buttocks of individuals with a spinal cord injury (SCI), who undergo pathoanatomical changes during the first months and years following the occurrence of the SCI, while sitting on a contoured foam cushion (CFC) that has been fitted close to the time of the injury but has not been replaced in subsequent years. DESIGN: Internal tissue loads in variant buttocks anatomies on a CFC were analyzed by means of finite element computer simulations. The pathoanatomical changes that are characteristic to SCI and were simulated here are: increase in fat tissue mass, intramuscular fat infiltration, muscle atrophy, and combinations of these conditions. SETTING: Computational biomechanical modeling. MAIN RESULTS: Simulating the aforementioned pathoanatomical changes consistently resulted in greater mechanical strain and stress magnitudes and more inhomogeneity in the loading state of muscle and fat tissues, with a more profound effect in fat. The simulations further indicated a clear trend of exacerbation in tissue exposure to loads as the pathoanatomical changes progress chronologically and the CFC is not replaced. CONCLUSIONS: A CFC that has been fitted at a time close to the SCI, but has not been replaced in subsequent years, substantially loses its efficacy in protecting patients from developing pressure ulcers and deep tissue injury in particular.